Tyrosine phosphatases regulate resistance to ALK inhibitors in ALK+ anaplastic large cell lymphoma - Karaca Atabay, Elif; Mecca, Carmen; Wang, Qi; Ambrogio, Chiara; Mota, Ines; Prokoph, Nina; Mura, Giulia; Martinengo, Cinzia; Patrucco, Enrico; Leonardi, Giulia; Hossa, Jessica; Pich, Achille; et al. (Blood, 2022)
Anaplastic large cell lymphomas (ALCLs) frequently carry oncogenic fusions involving the anaplastic lymphoma kinase (ALK) gene. Targeting ALK using tyrosine kinase inhibitors (TKIs) is a therapeutic option in cases relapsed after chemotherapy, but TKI resistance may develop. By applying genomic loss-of-function screens, we identified PTPN1 and PTPN2 phosphatases as consistent top hits driving resistance to ALK TKIs in ALK+ ALCL. Loss of either PTPN1 or PTPN2 induced resistance to ALK TKIs in vitro and in vivo. Mechanistically, we demonstrated that PTPN1 and PTPN2 are phosphatases that bind to and regulate ALK phosphorylation and activity. In turn, oncogenic ALK and STAT3 repress PTPN1 transcription. We found that PTPN1 is also a phosphatase for SHP2, a key mediator of oncogenic ALK signaling. Downstream signaling analysis showed that deletion of PTPN1 or PTPN2 induces resistance to crizotinib by hyperactivating SHP2, the MAPK, and JAK/STAT pathways. RNA sequencing of patient samples that developed resistance to ALK TKIs showed downregulation of PTPN1 and PTPN2 associated with upregulation of SHP2 expression. Combination of crizotinib with a SHP2 inhibitor synergistically inhibited the growth of wild-type or PTPN1/PTPN2 knock-out ALCL, where it reverted TKI resistance. Thus, we identified PTPN1 and PTPN2 as ALK phosphatases that control sensitivity to ALK TKIs in ALCL and demonstrated that a combined blockade of SHP2 potentiates the efficacy of ALK inhibition in TKI-sensitive and -resistant ALK+ ALCL.
Keywords: myši inbrední NOD; Humans; inhibitory proteinkinas; Mice, Inbred NOD; myši SCID; Antineoplastic Agents; Mice, SCID; Protein Tyrosine Phosphatase, Non-Receptor Type 2; lidé; zvířata; myši; Mice; Anaplastic Lymphoma Kinase; Protein Kinase Inhibitors; tyrosinfosfatasa nereceptorového typu 1; anaplastická lymfomová kináza; Crizotinib; Protein Tyrosine Phosphatase, Non-Receptor Type 1; Lymphoma, Large-Cell, Anaplastic; nádorové buněčné linie; protinádorové látky; tyrosinfosfatasa nereceptorového typu 2; krizotinib; Animals; Cell Line, Tumor; anaplastický velkobuněčný lymfom